(untitled) (International Journal of Engineering and Computer Science, 2017)
In digital image processing finding or searching a image in huge database of digital images is big task for designing more efficient image and shape matching algorithm. In data storage and image acquisition technologies we have to enabled the creation of large image datasets. In this type, it is necessary to develop appropriate information systems to efficiently manage these collections. The common approaches use the so-called Content-Based Image Retrieval (CBIR) systems. Basically, these systems try to retrieve images similar to a user-defined specification or pattern (e.g., shape sketch, image example). In this paper we see the different type’s techniques of content based image retrieval for different application purpose